MODEL PEMBELAJARAN ASSURANCE RELEVANCE INTEREST ASSESSMENTSATISFACTION (ARIAS) DALAM MATA PELAJARAN IPA PADA SISWA TUNANETRA - USMAYANI, RINDA (Jurnal Pendidikan Khusus, 2016)
Abstract Learning model of Assurance, Relevance, Interest, Assessment and Satisfaction (ARIAS) was the first effort in learning activity to plant trust sense to students. Trust attitude to the students could motivate them to behave achieving success. This research had purposes (1) to describe the learning process in learning model of Assurance, Relevance, Interest, Assessment, Satisfaction (ARIAS) in science lesson to the blind students in SDLB-A Tegalsari Surabaya, (2) to state the readiness done by the teacher in the implementation of learning model of Assurance, Relevance, Interest, Assessment, Satisfaction (ARIAS) in science lesson to the blind students in SDLB-A Tegalsari Surabaya, and (3) to describe the arrangement used as the evaluation instrument of learning model of Assurance, Relevance, Interest, Assessment, Satisfaction (ARIAS) in science lesson to the blind students in SDLB-A Tegalsari Surabaya. This research used descriptive method of qualitative approach and the technique of data collection applied observation, interview, and documentation. The data analysis used the steps of reduction data, display data, and verification / concluding. The research result indicated that (1) the learning process in learning model of Assurance, Relevance, Interest, Assessment, Satisfaction (ARIAS) in science lesson to the blind students in SDLB-A Tegalsari Surabaya could be applied well. The students were more active from the lesson before, (2) the readiness done by the teacher in learning model of Assurance, Relevance, Interest, Assessment, Satisfaction (ARIAS) in science lesson to the blind students in SDLB-A Tegalsari Surabaya was arranging syllabus, RPP, teaching material, and making assessment sheet (evaluation), (3) the evaluation arrangement in learning model of Assurance, Relevance, Interest, Assessment, Satisfaction (ARIAS) was the authentic assessment.   Keywords: Learning model of Assurance Relevance Interes  Assessment Satisfaction (ARIAS), Science,